Supplementation with mulberry leaves improves growth performance and meat quality of Xiangdong black goats - Yang Luo; Shuai Gao; Ao Sun; Jianbo Li; Haobang Li; Kangle Yi; Renke Hu; Bin Yang (Animal Bioscience)
Objective Mulberry (Morus alba) leaf (ML) is a high-quality feed source for ruminants, while it is unclear whether it can enhance the growth performance and meat quality of Xiangdong black goats. Methods In this study, we investigated the effects of ML supplementation (0%, 5%, 10%, 15%, and 20%) on the growth performance, serum variables, and the profiles of amino acids and fatty acids in the muscle of Xiangdong black goats. Results Results showed that the final body weight, initial and final dry matter intake, and average daily gain increased linearly and quadratically with the increasing ML content (p<0.05). The serum concentrations of total antioxidant capacity (T-AOC) increased linearly, while immunoglobulin G (IgG) increased quadratically with the increasing ML content (p<0.05). Conversely, the saturated fatty acids (SFA) content in meat decreased linearly with the increasing ML content (p<0.05). Compared to goats without ML supplementation, goats fed with 15% ML showed significant increases in serum concentrations of T-AOC, superoxide dismutase, catalase, and IgG (p<0.05). Furthermore, goats fed with 20% ML displayed significant decreases in SFA (C18:0) content, compared to goats without ML supplementation (p<0.05). Conclusion These results suggest that ML supplementation promotes the growth performance of goats. A diet containing 15% ML showed better effects in promoting antioxidant and immunomodulatory activities, while a diet with 20% ML was more effective in enhancing meat flavor in Xiangdong black goats.